ABOUT THE CHARACTERISTICS OF SIMILARITIES USED IN LINGUISTICS AND LITERATURE (Archive of Conferences, 2021)
This article discusses some of the analogies used in linguistics, fiction, and poetry, which are an important part of linguistics, and their activity in our language, as well as some of their peculiarities